PENDIDIKAN PELESTARIAN LINGKUNGAN HIDUP PERSPEKTIF AL-QUR’AN - Syahrul Munir (el-Moona: Jurnal Ilmu Pendidikan Islam, 2019)
The conclusion of this study about Living Environment Preservation Education in Al-Qur’an Perspective is one's attitude to the environment is Al-Quran has pointed principle of value and practical law in managing it, such as land potency use and its preservation. To maximize land potency, Al-Quran guides human being to optimize living environment as media to spread welfare for all living creatures in the earth. Al-Quran guides human being to maximize its use for their life. Therefore, to make it regularly beneficial for human being, it is not allowed to exploit it massively and brutally, particularly public resources and they are not owned by private. Al- Quran strictly prohibits human being to destroy land or earth since it has effect on degrading of living environment quality. In Al-Qur’an perspective that Living Environment has deep meaning for human being to save and preserve it, in consequence education for preserving environment should be reinforced either for formal or informal. Subsequently, people are highly aware that living environment preservation education is crucial for human being in the future. The interesting finding in this study is Al-Qur’an has concepts to manifest living environment, they are: 1) Obligate to save animal from extinction, 2) Obligation to preserve and save animal, 3) Planting and reforestation of tree, 4) Reactivate died land, 5) Keep clean, 6) Keep air clean, 7) Save for water use, 8) Avoid devastation and Keep nature balancing. This study aims to analyze the importance of living environment preservation education according to Al-Qur’an perspective. Many Al-Qur’an and Hadith verses expose the eminence in preserving and saving it. It is library research, Al-Quran and interpretation books (classic and contemporary) as primary source, while the secondary ones are books, journals, and articles have correlated to this research object. This research uses Al-Qur’an- qualitative based.